(untitled) (Sciences & Technology. A, exactes sciences, 2007)
This publication aims to present a study of the current–voltage characteristics of organic solar cell based on a composite of poly (2-methoxy-5-(2’-ethylhexyloxy)-1, 4-phenylenevinylene (MEH-PPV) with [6, 6]-phenyl C60 butyric acid methyl ester (PCBM) as a function of illumination intensity. The variation of the photocurrent, the fill factor, the open-circuit voltage, the saturation current and the maximum output power under different light intensity values (100 mW/cm2, 60 mW/cm2 and 24 mW/cm2), were investigated experimentally. It is observed that for given values of series and/or shunt resistance, the fill factor is determined by reverse saturation current and diode quality factor of the solar cell. The effects of these components on the overall photovoltaic performance are discussed.